MORPHO-FUNCTIONAL STATE OF RATS PINEAL GLAND AND SUPRACHIASMATIC NUCLEUS OF HYPOTHALAMUS AFTER DIFFERENT REGIMES OF EXOGENOUS MELATONIN ADMINISTRATION - KALMUKOVA, O.; DZERZHYNSKY, M. (Bulletin of Taras Shevchenko National University of Kyiv. Biology, 2025)
In modern society increase of digitalization associated with grown exceed level of light at night – a new type of pollution. Presence of light at night inhibited endogenous melatonin synthesis by pineal gland, that influence on circadian system work cycles, so organism oftenbroken regime of wake/sleep, meals, physical activity. Also, a lack of melatonin in some certain time of dayand low melatonin concentration both, were shown take some intervention in diseases development through incorrect regulation of clock-depended genes expression. In connect with this, some latest clinical protocol in therapy or clinical trials of many different pathologies (for example, insomnia, metabolic syndrome, cardiovascular diseases, central nervous and immune system trouble, cancer, viral infection, etc.) include exogenous melatonin usage. As melatonin perform his function via endocrine and paracrine ways in variety types of cell, his application take place in wide range of doses and in different time of day (chronotherapeutic approach). Therefore, important to control state of circadian system central elements – pineal gland (main producer of endogenous melatonin) and suprachiasmatic nucleus (SCN) of hypothalamus (central pacemaker of circadian rhythm) in conditionsof exogenous melatonin treatment. Thus, the main goal of our research were analysis of rats pineal gland and hypothalamic SCN morpho-functional state after different time (morning, evening and continuously with drinking water) melatonin daily administration. Melatonin was administered by gavage for 7 weeks in dose 30 mg/kg 1 h before lights-off (M ZT11, evening), or 1 h after lights-on (M ZT01, morning), or continuously with drinking water during day-night period (MW). After melatonin use only in MW group pineal gland demonstrates changes in morphology (pinealocytes nucleus had mild basophilic color) and morphometric (increased cross-sectional area of the pinealocytes nucleus in compare with control group) analysis data. Besides, some similar changes were observed in SCN: the cross-sectional area of the SCN neurons nucleus grown in case of usage each of regime melatonin administration, while morphology characteristic remains without any alteration. In general, it suggesting about having by melatonin non-inhibiting features in context of circadian system feedback loop and supposing wide potential for melatonin use with absent huge side effect on central elements of above mentioned system.